2019
DOI: 10.1111/jfb.14108
|View full text |Cite
|
Sign up to set email alerts
|

Enteromius thespesios (Teleostei: Cyprinidae): a new minnow species with a remarkable sexual dimorphism from the south‐eastern part of the Upper Congo River

Abstract: A new minnow species, Enteromius thespesios, is described from the south-eastern part of the upper Congo River; that is, the Kalule Nord, the Luvilombo and the Chambeshi Rivers. Enteromius thespesios belongs to the group of the soft-rayed species of Enteromius from the Congo Basin; that is, those with a weakly ossified, flexible last unbranched dorsal-fin ray that lacks serrations along its posterior edge. Within this group, E. thespesios is most similar to E. humeralis, from which it is distinguished by a hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…The unrecognised diversity found within species complexes in various systems (e.g., Schmidt et al 2017Schmidt et al , 2019Van Ginneken et al 2017), the revalidation of species as found in our study and the study of Schmidt et al (2018), and the description of new species, such as E. pinnimaculatus from Gabon (Mipounga et al 2019) and E. thespesios from the Upper Congo River (Katemo Manda et al 2019) all suggest that the species richness of Enteromius is much larger than currently thought. Hence, the present number of 211 valid species of Enteromius (Froese & Pauly 2019), is certainly a considerable underestimation of the real species diversity.…”
Section: Unknown Diversity In Enteromiusmentioning
confidence: 43%
“…The unrecognised diversity found within species complexes in various systems (e.g., Schmidt et al 2017Schmidt et al , 2019Van Ginneken et al 2017), the revalidation of species as found in our study and the study of Schmidt et al (2018), and the description of new species, such as E. pinnimaculatus from Gabon (Mipounga et al 2019) and E. thespesios from the Upper Congo River (Katemo Manda et al 2019) all suggest that the species richness of Enteromius is much larger than currently thought. Hence, the present number of 211 valid species of Enteromius (Froese & Pauly 2019), is certainly a considerable underestimation of the real species diversity.…”
Section: Unknown Diversity In Enteromiusmentioning
confidence: 43%
“…The Congo Basin is home to the largest overall fish species diversity of the African continent in general and also harbours a large number of endemic species (Snoeks et al ., 2011; Stiassny et al ., 2011). Despite this great species diversity and important endemism, there is growing evidence indicating that the current taxonomy underestimates the species diversity of freshwater fishes in the Congo Basin as many parts of it, including the Upper Lualaba, remain poorly explored (Abwe et al ., 2019; Katemo Manda et al ., 2018, 2019; Schedel et al ., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…BTs are keratin‐based epidermal nodules, the development of which has been found to be associated with the production of androgen hormones (Kortet et al ., 2003; McMillan et al ., 2013). These white tubercles appear in farmed and wild males of Knodus Eigenmann (Characidae: Stevardiinae) (Menezes & Marinho, 2019), Enteromius thespesios (Teleostei: Cyprinidae) (Katemo Manda et al ., 2020) and the pale chub Zacco platypus (Pisces: Cyprinidae) (Takahashi, 2018). It has previously been suggested that these tubercles could play roles in conspecific recognition, protection against mechanical injury and defence of nests and territories (Kortet et al ., 2004; Poncin et al ., 2011).…”
Section: Introductionmentioning
confidence: 99%